A Narrative Study on Poverty Alleviation by Volunteer Teachers in Rural Schools - HUANG Rong; WANG Nan (Jiaoshi jiaoyu xuebao)
Volunteer teaching is an important measure to support the development of rural education. Narrative research is a method of explaining the volunteer teachers' behavior and its significance. As the most important resource of rural education, volunteer teachers have played an important role in consolidating and expanding the achievements of poverty alleviation and blocking the transmission of poverty between generations. As a component of volunteer teachers in rural schools, graduate student assistance teaching groups have their unique characteristics compared with other types of volunteer teachers. In taking root in rural society and serving rural education, they bear the dual role of "teaching" the students in poverty-stricken areas, as well as "being taught" in teaching practices. From the education practice of "being a teacher" to poverty alleviation thinking of "dual support of aspiration and knowledge", then to the deep interaction between teaching and learning of "teaching is also being taught", a benign interaction mode of education assistance and teacher growth has been formed among them. In the effective connection between consolidating and expanding the achievements of poverty alleviation and accelerating the comprehensive of rural revitalization, it is necessary to continuously improve the support mechanism of graduate student assistance teaching groups from both internal and external aspects, so as to better leverage the power of volunteer teaching.